Standard Setting and Following in Corporate Governance: An Observation-Theoretical Study of the Effectiveness of Governance Codes - Seidl, David (Organization (London, England), 2007)
Researchers have lately been pointing out the increasing significance of standards in all areas of contemporary life. There have been calls for more research into the processes of setting and following standards. In this article we analyse the effectiveness of codes of corporate governance as a specific type of standard that has become particularly prominent over the last decade. On the basis of an observation-theoretical approach, codes are conceptualized as schemas of observation that establish a field of mutual observations. The effectiveness of codes depends on the one hand on the extent to which they become integrated into recursive cycles of mutual observation between the corporation and the various actors in the field. On the other hand, effectiveness depends on how codes relate to other observational schemas. On the basis of the analysis several propositions about the effectiveness of code regulation are developed, which may be tested in further empirical studies.